Infodemiology on diet and weight loss behavior before and during COVID-19 pandemic in Indonesia: Implication for public health promotion - Ramadhani, Ira Dewi; Latifah, Leny; Prasetyo, Andjar; Khairunnisa, Marizka; Wardhani, Yurika Fauzia; Yunitawati, Diah; Fahlevi, Mochammad (Frontiers in Nutrition, 2022)
Objective: This study would explore public interest through information search trends on diet and weight loss before and during the COVID-19 pandemic in Indonesia. Methods: The Google Trends database was evaluated for the relative internet search popularity on diet-related search terms, including top and raising diet-related terms. The search range was before and during the COVID-19 pandemic (April 2018 to January 2022) in the Indonesia region. We analyzed the Relative Search Volume (RSV) data using line charts, correlation, and comparison tests. Results: Search queries of “lose weight” was higher during the pandemic (58.34±9.70 vs 68.69±7.72; p<0.05). No difference was found in diet-related searches before and after the pandemic. Public interest in the diet was higher after Eid al-Fitr (Muslims break fasting celebration day) and after the new year. Many fad diet (FD) terms were found on the top and raising terms. Conclusion: After Eid al-Fitr and the new year were susceptible times for promoting a healthy diet in Indonesia. Potential need found before those times for education in inserting healthy food among fatty and sugary menus related to holidays and celebrations. Higher interest in “lose weight” was relevant with heightened obesity risk during the social restriction and heightened COVID-19 morbidity and mortality due to obesity. The high interest for rapid weight loss through FD needs to be resolved by promoting healthy diets with a more captivating message and messenger, like using consistently top terms in the keywords of the official healthy guidance diet. Future research could explore the relation between a diet with other behavior or with non-communicable diseases.